Reduksi Kecacatan Produk Kembang Tahu Menggunakan Gugus Kendali Mutu dan FMEA - Ikhwana, Andri; Jami, Hikmatu (Jurnal Kalibrasi, 2025)
This study aims to provide recommendations for improvements to reduce the defect rate in the tofu production process at PD Mulya Mandiri. This study was motivated by the high defect rate, which has an impact on operational efficiency and production quality. The Quality Control Circle (QCC) method with the Seven Tools and Failure Mode and Effect Analysis (FMEA) approaches were used to identify the main causes of product defects and determine effective improvement measures. The analysis was conducted through the collection of defect data, the creation of a Pareto chart, and the tracing of root causes using a cause-and-effect diagram. FMEA was applied to evaluate the potential risk of failure and set improvement priorities based on the Risk Priority Number (RPN). The results of this study identified the main causes of defects and provided recommendations for improvement. The implementation of these solutions is expected to reduce the defect rate by up to 3% and improve product quality consistency. It is hoped that the results of this study can be used as a reference for the application of more optimal quality control strategies in the production process.